(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2024)
The article analyzes the civil liability system in the draft reform of the Civil Code, focusing on the logic of imputability of damage and the guarantee of credit receipt. The author, rapporteur of the reform, discusses how the legal system should ensure the patrimonial balance of the injured party and addresses innovations in real guarantees, essential for legal certainty in modern private relations. (Received: July 2024 | Accepted: October 2024)